Design and Analysis of Dual Narrow Band MIMO (DNB-MIMO) Antenna for IoT Applications - Thiruvenkadam, Saminathan; Parthasarathy, Eswaran (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A compact DNB-MIMO antenna design and analysis for IoT application was proposed. The antenna radiator consists of 2 L-shaaped quarter-wavelengths and inverted 7-shaped radiators with a microstrip feed line, and partial ground plane with a size of 32 × 15 mm2. This antenna achieves a higher quality factor (Q > 10) and narrow band impedance matching at the central frequencies of 1.8 GHz and 2.4 GHz bands with approximately 8.2% and 6.2% bandwidth respectively. The suitability of the designed antenna for IoT applications is verified through the hosting device model. The proposed 4-port MIMO antenna has an overall size of 60 × 60 ×1.6 mm3, and it is printed on an FR4 substrate. The diversity add comma such as ECC, DG, TARC, MEG, and CCL, are calculated and there values are < 0.19, 9.85 dB, < -25 dB, < -6 dB, < 0.19 bits/Hz/s, respectively, within the limits. The proposed antenna is integrated with the Zigbee module (lowercase) to analyze the performance for IoT applications at 2.4 GHz